Designação e argumentação em uma ação popular da cidade de São Carlos - Canassa, Marcela Codognatto (Universidade Federal de São Carlos, 2007)
This work is developed with the perspective theory and methodology of the Semantics of happening and has the objective to understand how to work the designation of language, more specificaly, to analyze how to work to the juridical argumentation through the designations. As an example we took as an analyze object a juridical process named Ação Popular 2, where the petitioner locutors ask the preservation of the public square Coronel Paulino Carlos de Arruda Botelho, where the one who were required were building commercial points to ambulant commmerce. In conclusion we contacted that there is two relations of antonym in this process that mobilized the argumentation. A big one which happen between the enunciation of the petitioners locutors and those used by who were required; and a specific one, which happen in the interior of the enunciation of the petitioners locutors which through of the deignations and of the memorables, guide the argumentation in favor of the preservation of the Square Paulino Carlos as historic patrimony of the city, and so the square stays as the space of the local identity preservation.
Keywords: Semântica; Designação; Lógica; Texto jurídico; Semantics; Designation; Argumentation; Juridical text; LINGUISTICA, LETRAS E ARTES::LINGUISTICA